Disintegrating perineal disease: A variant of watering-can perineum - N. Abrol; A. Devasia (African Journal of Urology, 2014)
Watering-can perineum is a known complication of inflammatory urethral stricture disease. We report a case of disintegrating perineal disease, a fulminant variant of watering-can perineum, in an immunocompetent patient.